Spectral enhancement in optical parametric amplifiers in the saturated regime - Bigourd, D; Patankar, S; Robbie, S; Doyle, H; Mecseki, K; Stuart, N; Hadjicosti, K; Leblanc, N; New, G; Smith, R (2013)
We present numerical and experimental studies on a front-end laser system for seeding a sub-picosecond multi-terawatt/petawatt light source based on two highly saturated optical parametric amplifiers. Numerical results showing energy gain, spectral gain, and stability as saturation is approached are presented. An experimental realisation of the system has been constructed, and its performance has been found to be in good agreement with the numerical simulations. The total gain is in excess of 105 over a few picosecond gain window, and the pulse energy is ∼100 μJ with 4 % root mean square stability. © 2013 Springer-Verlag Berlin Heidelberg.